A Case Study of Dholuo Anaphors using Relevance Theory - Onyango, Janet Achieng’; Nandelenga , Henry Simiyu (Progress in Language, Literature and Education Research Vol. 9, 2024)
This paper aims to investigate the interpretation of anaphors in Dholuo in different contexts to ascertain their relevance in utterances. A number of studies on languages all over the world indicate the presence of anaphors such as reflexives and reciprocals. These anaphors occupy different positions with regard to their occurrence, hence determining their varied interpretations. This could probably be due to anaphors deriving reference from the antecedent that occurs before them in an utterance. These anaphors are also marked as morphemes or lexically marked. Dholuo an African language, for instance, marks the reflexive and the reciprocal by the same morpheme, which poses some ambiguity in their interpretation. A descriptive design was employed to describe the anaphors using Relevance Theory (RT) as the tool for analysis. The corpus of primary data used in this paper consists of a string of sentences with anaphors elicited through the researcher’s intuition as a native speaker, and also from the participants through semi-structured interviews. In order to ensure validity, data was verified by six adult native speakers selected through a purposeful sampling technique. Data collected was presented systematically and then analyzed procedurally. RT Cognitive and Communicative Principles were employed to describe the relevance of the anaphoric utterances in the utterance. To guarantee a clear interpretation of the utterance in various situations, a Relevance Comprehension Procedure (RCP) was added. The outcome shows that when context is added, Dholuo anaphors can be distinguished between reflexives and reciprocals. Because the anaphora is used so frequently, it is clear that both the speaker and the listener understand the utterance's inferred meaning. However, RT may fail to provide an immediate interpretation of the utterance with the prevailing context. This led to violation of the RCP as more contexts are presented to ensure the right interpretation is reached. This calls for the theory to accommodate utterances that require a lot of effort to interpret.